2021
DOI: 10.1123/ijspp.2020-0662
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Training Load Quantification Methods on the Fitness-Fatigue Model

Abstract: Purpose: Numerous methods exist to quantify training load (TL). However, the relationship with performance is not fully understood. Therefore the purpose of this study was to investigate the influence of the existing TL quantification methods on performance modeling and the outcome parameters of the fitness-fatigue model. Methods: During a period of 8 weeks, 9 subjects performed 3 interval training sessions per week. Performance was monitored weekly by means of a 3-km time trial on a cycle ergometer. After thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…It is known, however, that an individual model fit is necessary when trying to relate TL and performance. 12 In literature, values are found ranging from 4 to 51, and from 4 to 74 for τ 1, and τ 2 , respectively. 2,4,[12][13][14][15] Although some coaching platforms enable coaches to adjust these values to the user's preference, it is futile to estimate what parameter values will best suit the individual athlete without fitting the model.…”
Section: Use Of the Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known, however, that an individual model fit is necessary when trying to relate TL and performance. 12 In literature, values are found ranging from 4 to 51, and from 4 to 74 for τ 1, and τ 2 , respectively. 2,4,[12][13][14][15] Although some coaching platforms enable coaches to adjust these values to the user's preference, it is futile to estimate what parameter values will best suit the individual athlete without fitting the model.…”
Section: Use Of the Modelmentioning
confidence: 99%
“…Moreover, studies have shown that different input variables (ie, TL calculations) can lead to substantially different results in the parameter values. The study of Mitchell et al 13 and the study of Vermeire et al 12 have both shown that the input of different TL quantification methods will lead to different τ values on the same data set. The parameter values of these studies differ considerably from the original papers, which gives rise to question the validity of the commonly used parameter values.…”
Section: Use Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Since FFMs are sensitive to the nature of the model input [ 25 ], a consistent training quantification method that is not biased by the type of training is required across training sessions.…”
Section: Fitness-fatigue Model and Conceptual Issuesmentioning
confidence: 99%